Hyperspectral / multispectral imaging technology: application for pomegranate fruit internal quality evaluation and bruise detection - Okere, Emmanuel (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.